LEGAL NATURE OF REGULATORY LEGAL ACTS OF THE MINISTRY OF INTERNAL AFFAIRS OF UKRAINE - Slynko, D. V. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article is devoted to the study of the legal nature of the normative legal acts of the Ministry of Internal Affairs of Ukraine. The analysis of the legal literature devoted to the study of these acts is carried out. Specificity of normative legal acts of the Ministry of Internal Affairs of Ukraine is considered. It is determined that departmental acts of the Ministry of Internal Affairs of Ukraine are subordinate acts issued on the basis and in accordance with the law with a view to concretizing legislative prescriptions, clarifying them or establishing primary norms and are management acts of a state body that is endowed with special functional competence.